Voices from Students: How do EFL Students Perceive the Implementation of Group Work in the Students-Created Video Speaking Project - Erny Selfina Nggala Hambandima; Eka Merdekawati Imelda Seseli; Alfred Snae (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
This research investigates students’ perceptions of using group work and student-created videos in a Speaking for Professional Communication course. Working in groups of 4–5 members, students collaborated to produce video projects and role-play authentic situations. Data were collected through video documentation and questionnaires and analysed using descriptive and qualitative content analyses. The findings indicate that group work offers several significant educational benefits. It promotes students' creativity through collaborative idea generation and problem-solving, enhances communication skills by encouraging discussion and constructive interaction, and strengthens teamwork through shared responsibility and cooperation. In addition, collaborative learning improves students' understanding of the course content by allowing them to learn from peers and exchange different perspectives. Most importantly, group work creates meaningful learning experiences by fostering active engagement, increasing confidence, and developing essential interpersonal and collaborative competencies that extend beyond the classroom. It is also viewed as effective because it supports easier problem-solving, produces higher-quality outcomes, encourages open communication, boosts motivation, and promotes ongoing feedback. The findings revealed that students viewed the teacher's implementation of group work positively. They reported that the instructional approach facilitated effective communication by encouraging the exchange of ideas, strengthened collaboration through shared responsibilities and peer interaction, and enabled the teacher to identify students' academic challenges, monitor group dynamics, and provide appropriate instructional support. Additionally, students prefer group work because it helps build leadership, presentation, confidence, and motivation, making learning more active, engaging, and effective.